RUTIN - Atmojo, Joseph Peter; Sumerjana, Ketut; Wiyati, Wahyu Sri (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Rutin is a composition inspired by the anxiety felt by the creator. This restlessness results from activities or work that are carried out repeatedly, causing a feeling of boredom and ultimately this feeling can be eliminated by no longer doing activities or work as before. Using the concept of modern music, namely music that uses instruments and technology. The instruments used in Routin's work consist of 3 electric guitars, electric bass, and drums. The artist uses a guitar playing technique with the addition of a delay effect which produces a repetition of the sound of what is played and utilizes the results of the repetition of the sound so that the resulting sound seems different to what is actually played. In order for Routine compositional works to be created academically, the creator refers to one creation method written down by the Arts Consortium, namely: (1) preparation, (2) elaboration, (3) synthesis, (4) realization of the concept, and (5) completion into the final form artworks. Some of the works that the creator used as references include, (1) Rob Scallon's work entitled Rain, (2) Ewan Dobson's work entitled Time 2, (3) Steve Reich's composition work entitled Electric Counterpoint, (4) Steve Reich's composition work entitled 2x5, (5) Work from the band Netral or NTRL entitled Flying Sink and Pertermpuran Hati, (6) Work from the band The Temper Trap entitled Sweet Disposition, (7) Work from the band Animal as Leaders entitled Red Miso.